Effect of Islamic corporate governance on the relationship between pressure, opportunity, rationalization, capability and banking fraud in selected banks in Nigeria: a pilot test - D. Yusuf, Ali; Ahmad, Umar; Ahmad Razimi, Mohd Shahril (Science Publications, 2016)
The aim of this paper is to examine a few sample data on the effect of Islamic corporate governance on the relationship between pressure, opportunity, rationalization, capability and banking fraud in selected banks in Nigeria.Thus, instruments such as content and face validity,reliability and the data normality were also examined based on the on revised version by an expert, a few data were analyzed using the statistical software SPSS version 17.The result reveals that the instruments are reliable and the data for pilot study show evidence of rational normality.